Revisiting Classical 3 beta-hydroxysteroid Dehydrogenase 2 Deficiency: Lessons from 31 Pediatric Cases - BEREKET, ABDULLAH; HAKLAR, GONCAGÜL; ŞİRİKÇİ, ÖNDER; DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY (ENDOCRINE SOC, 2020)
Context: The clinical effects of classical 3 beta-hydroxysteroid dehydrogenase 2 (3 beta HSD2) deficiency are insufficiently defined due to a limited number of published cases. Objective: To evaluate an integrated steroid metabolome and the short- and long-term clinical features of 3 beta HSD2 deficiency. Design: Multicenter, cross-sectional study. Setting: Nine tertiary pediatric endocrinology clinics across Turkey. Patients: Children with clinical diagnosis of 3 beta HSD2 deficiency. Main Outcome Measures: Clinical manifestations, genotype-phenotype-metabolomic relations. A structured questionnaire was used to evaluate the data of patients with clinical 3 beta HSD2 deficiency. Genetic analysis of HSD3B2 was performed using Sanger sequencing. Novel HSD3B2 mutations were studied in vitro. Nineteen plasma adrenal steroids were measured using LC-MS/MS. Results: Eleven homozygous HSD3B2 mutations (6 novel) were identified in 31 children (19 male/12 female; mean age: 6.6 +/- 5.1 yrs). The patients with homozygous pathogenic HSD3B2 missense variants of > 5% of wild type 3 beta HSD2 activity in vitro had a non-salt-losing clinical phenotype. Ambiguous genitalia was an invariable feature of all genetic males, whereas only 1 of 12 female patients presented with virilized genitalia. Premature pubarche was observed in 78% of patients. In adolescence, menstrual irregularities and polycystic ovaries in females and adrenal rest tumors and gonadal failure in males were observed. Conclusions: Genetically-documented 3 beta HSD2 deficiency includes salt-losing and non-salt-losing clinical phenotypes. Spared mineralocorticoid function and unvirilized genitalia in females may lead to misdiagnosis and underestimation of the frequency of 3 beta HSD2 deficiency. High baseline 17OHPreg to cortisol ratio and low 11-oxyandrogen concentrations by LC-MS/MS unequivocally identifies patients with 3 beta HSD2 deficiency.
Keywords: 3 beta HSD2 deficiency; CAH; HSD3B2; adrenal insufficiency; children; CONGENITAL ADRENAL-HYPERPLASIA; HSD3B2 GENE; 11-OXYGENATED ANDROGENS; MOLECULAR-BIOLOGY; MUTATION; TUMOR